COMPARATIVE STUDY OF SOME BIOCHEMICAL PARAMETERS AMONG OF COVID-19 SYMPTOMS AND NON COVID-19 SYMPTOMS INDIVIDUALS - K.Rostam, Shkar Rzgar; Shekhany , Khattab Ahmed Mustafa; Smail, Harem Othman (Biology Department, Faculty of Mathematics and Natural Sciences, Sriwijaya University, 2020)
Nowadays in the Kurdistan region of Iraq, the number of patients have common symptoms with COVID-19 infection rapidly increased. 123 patients which they had common symptoms with COVID-19 and 94 healthy control individuals (non-COVID-19) were subjected for quantitative analysis for each one of the following biochemical parameters, Lactate dehydrogenase (LDH), Creatine Phosphokinase (CPK), and C-reactive protein (CRP) in Erbil, Kurdistan Region of Iraq. We analyze clinical features and compared the differences between COVID-19 and non-COVID-19 symptoms. Among the healthy control individuals, the absolute value of LDH, CPK Creatine Kinase and CRP were determined in between the normal range, and in compare with patients with COVID-19 symptoms their values were smaller and, the P value was (P ＜0.05). All three biochemical parameters increased among patients with COVID-19 symptoms, but more significantly, steadily increase was observed only in LDH value in age above and under 40 years (284.43±10.29 and 321.23±16.32 U/L), and p-value was (0.0488). Male patients had higher levels of LDH (299.32±11.42 U/L), CPK Creatine Kinase (195.90±26.65 mg/L), and C-Reactive Protein (5.86±3.96 mg/L) in compared with the female patients. Our study suggested that among patients who have COVID 19 symptoms, increased LDH is the advised and helpful biochemical marker among routine panel for COVID-19 infection evaluation. Also, CRP levels were positively correlated with male patients when compared with the healthy control.